Persepsi Ancaman dan Tren Sumber Daya Hutan dan Faktor yang Mempengaruhi Pembalakan di Hutan Omo, Negara Bagian Ogun, Nigeria - Adedigba, Bolaji Kofoworola; Oyetayo, Oyelowo; Olukemi, Adebayo Dorcas; Olaitan, Ahmed Ahmed; Olubunmi, Oke Deborah; Bukola, Adesogan Damilola (Jurnal Ilmu Kehutanan, 2025)
This research investigated rural households' views on threats to sustainable forest management and the factors influencing logging in the Omo Forest Reserve Area, which has been experiencing deforestation and unsustainable utilization. The researchers interviewed 300 household heads and validated 276 responses for Ordinary Least Squares Regression and quantitative summaries, including percentages, frequencies, and bar charts. The results showed that most households were male-headed (92.8%) and married (87.3%), with primary and secondary education accounting for 29.7% and 39.2%, respectively. Male-headed households made up 92.8%, and 7.2% were female-headed households. Approximately 50.7% considered logging a significant threat to forest sustainability, while 48.6% viewed the failure to replant as a serious problem. A total of 18.48% perceived indiscriminate grazing by nomadic herders as a serious threat. Other factors included urbanization, agriculture, and fuelwood collection, all of which posed threats to forest management. Regression analysis yielded a coefficient of determination (R²) of 0.67, suggesting that sex, secondary occupation, age, and length of settlement in forest areas significantly influenced wood logging. Measures such as awareness campaigns, discouraging indiscriminate logging, and enforcing policies are recommended to address these challenges.